2020
DOI: 10.1519/jsc.0000000000003130
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Different Weekly Sets-Equated Resistance Training Frequencies on Muscular Strength, Muscle Mass, and Body Fat in Older Women

Abstract: Pina, FLC, Nunes, JP, Schoenfeld, BJ, Nascimento, MA, Gerage, AM, Januário, RSB, Carneiro, NH, Cyrino, ES, and Oliveira, AR. Effects of different weekly sets-equated resistance training frequencies on muscular strength, muscle mass and body fat in older women. J Strength Cond Res 34(10): 2990–2995, 2020—The aim of this study was to analyze the effects of different resistance training (RT) frequencies (2 vs. 3 times per week) with an equivalent number of weekly sets performed between conditions on muscular stre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
21
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 26 publications
(24 citation statements)
references
References 24 publications
2
21
0
1
Order By: Relevance
“…However, the hypothesis that these occurred due to possible overtraining should not be dismissed. Although we opted for using a relatively high volume in the 24 weeks of RT because we had observed that this seems to be ideal for inducing optimal adaptations in the outcomes studied herein for this population [12,[23][24][25][26][27][28], the use of such training protocol might have exceeded the ideal training dose for some participants. Moreover, the presence of the ALT group, which performed the same EO throughout the 24 weeks of RT, allows us to believe that simply changing the EO after a 12-week training period does not influence the responses to training.…”
Section: Discussionmentioning
confidence: 99%
“…However, the hypothesis that these occurred due to possible overtraining should not be dismissed. Although we opted for using a relatively high volume in the 24 weeks of RT because we had observed that this seems to be ideal for inducing optimal adaptations in the outcomes studied herein for this population [12,[23][24][25][26][27][28], the use of such training protocol might have exceeded the ideal training dose for some participants. Moreover, the presence of the ALT group, which performed the same EO throughout the 24 weeks of RT, allows us to believe that simply changing the EO after a 12-week training period does not influence the responses to training.…”
Section: Discussionmentioning
confidence: 99%
“…Strategies to reduce regional body fat are then deemed necessary. Previous RT interventions with durations of 12 and 24 weeks showed reductions in android fat of −3% [ 28 ] and −12% [ 29 ] in untrained older women, indicating a benefit for the RT, and that training effects may be dose-response [ 24 , 30 ]. In parallel, we observed a reduction in android fat of 8% and 4% for WPR and NPR, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…Of the different body regions exposed to RT, 23 studies implemented full-body RT [32][33][34][35][36][37][38][39][40][41][43][44][45][46][47][48][49][50][51][52][53][54][55], and 3 implemented lower body RT [9, 31,42]. Thus, only the areas of the body which underwent the RT intervention have been examined by the afore mentioned screening tools.…”
Section: Search Outcomesmentioning
confidence: 99%